1 Corinthians - Bender, Kimlyn J. 1969- (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2022)
"A leading theologian offers a theological reading of 1 Corinthians in this addition to the Brazos Theological Commentary on the Bible"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Commentaries